Human genes and genomes : science, health, society - Rosenberg, Leon E., 1933-; Rosenberg, Diane Drobnis, 1944-; ScienceDirect eBooks (Amsterdam : Elsevier/Academic Press, 2012)
In the nearly 60 years since Watson and Crick proposed the double helical structure of DNA, the molecule of heredity, waves of discoveries have made genetics the most thrilling field in the sciences. The study of genes and genomics today explores all aspects of the life with relevance in the lab, in the doctor's office, in the courtroom and even in social relationships. In this helpful guidebook, one of the most respected and accomplished human geneticists of our time communicates the importance of genes and genomics studies in all aspects of life. With the use of core concepts and the integration of extensive references, this book provides students and professionals alike with the most in-depth view of the current state of the science and its relevance across disciplines. Bridges the gap between basic human genetic understanding and one of the most promising avenues for advances in the diagnosis, prevention and treatment of human disease. Includes the latest information on diagnostic testing, population screening, predicting disease susceptibility, pharmacogenomics and moreExplores ethical, legal, regulatory and economic aspects of genomics in medicine. Integrates historical (classical) genetics approach with the latest discoveries in structural and functional genomics.
Framing the Field -- Introducing the Core Concepts -- Genetic Variability -- Growth, Development, and Reproduction -- Transmission of Genes -- Structure of Genes, Chromosomes, and Genomes -- Expression of Genes and Genomes -- Mutation -- Biological Evolution -- Human Individuality -- Chromosome Abnormalities -- Single Gene Defects -- Multifactorial Traits -- Disorders of Variable Genomic Architecture -- Birth Defects -- Cancer: Germ Line and Somatic Mutations -- Detection and Treatment -- Population and Evolutionary Genetics -- Personalized Genetics and Genomics.
Title from PDF title page (viewed May 21, 2012).
Includes bibliographical references (pages 373-378) and index.
Elsevier
Keywords: Human genetics; Medical genetics; Human genome; Genomics; genome; SOCIAL SCIENCE -- Anthropology -- Physical; Genomics; Human genetics; Human genome; Medical genetics; Genetic Phenomena; Genetic Diseases, Inborn; Genomics; Genetics; Genome, Human; Electronic books